Digitalizacija in izkušnje pravnikov v Italiji - Jarc, Marco (Podjetje in delo, 2022)
Digitalisation was first mentioned in Italian legal acts in the early 1990s. The judicial system also began to adapt to the needs of modern society. Particularly in the past decade, reforms were moving towards digitalisation. Despite the large investments that the state has allocated for these purposes, the results are modest, as Italy is in the lower half of the Digital Economy and Society Index (DESI) of the European Commission. In the judicial system, Italy is recording decisive shifts in the direction of digitalisation and modernisation. Since 2014, the civil procedure has been fully informatised and is significantly more efficient. Digitalisation of procedures has also relieved the work in courts and law offices. The informatic systems, which were created according to the model of the analogue procedure, still have major flaws that lawyers face on a daily basis. The investments foreseen by the Italian state in the context of the Recovery and Resilience Plan for the relaunch of digital innovation are expected to be used for the required modernisation of the digital infrastructures both in the public and the private sector.
Keywords: digitalisation; Digitalizacija; electronic certified mail; electronic civil procedure; elektronska certificirana pošta; elektronski civilni postopek; Italija; Italy